Ukraine Investment Security Mechanism: State and Ways of Improvemen (Economics and region, 2019)
The state of the ensuring mechanism of the investment security of Ukraine is investigated. Defects that impede the effective functioning of the ensuring mechanism of investment security of the state, which include the deficiencies of state regulation of all key functions of public policy – from monitoring to controlling its implementation, evaluation of efficiency and effectiveness. Two alternatives are proposed. The first one is to maintain the situation with expressed shortcomings and blunders of institutionalization of investment security. The second – with their elimination and eventually formation of the bases of the investment security system of Ukraine as a functional and structural element of the higher level system – the economic security of the state, ensuring complex institutionalization of the investment security of Ukraine with "fuses" of key risks and threats.
Keywords: institutionalization; security mechanism; deviant behavior; shadow economy; investment security; economic security